A Term Female Neonate with Achondroplasia: A Case Report - Arun P; Vijayalaxmi Gagandeep; Md. Khaja Moinuddin; Nagabhushan BM (JCDR Research and Publications Pvt. Ltd., 2017)
Achondroplasia is one of the commonest causes of dwarfism, inherited as autosomal dominant trait. Majority of the cases are due to mutation in the Fibroblast Growth Factor Receptor 3 (FGFR3). The mutation results in gain of FGFR3 function, which affects cartilaginous growth plate in the growing bone causing the skeletal changes. At birth it manifest as short limbs, large head with midfacial hypoplasia and narrow trunk. Diagnosis is mainly based on clinical features and skeletal radiography. Complications are hypotonia, delayed development, hydrocephalus, recurrent ear infections and dental malocclusion.